Blinding in trials of interventional procedures is possible and worthwhile - Wartolowska, K; Beard, D; Carr, A (F1000Research, 2018)
In this paper, we have used evidence from our earlier review of surgical randomised controlled trials with a placebo arm to show that blinding in trials of interventional procedures is feasible, and that many creative methods can be used to make the active and the placebo procedure as similar as possible. We give examples of ingenious strategies used to simulate the active procedure and make the placebo control indistinguishable from the active treatment. We discuss why it is important to blind of patients, assessors, and caregivers and the types of bias that may occur in interventional trials. Finally, we describe the benefits of blinding, from the obvious ones such as avoiding bias, as well as less evident benefits such as avoiding patient drop out in the control arm.